Complete Edition (n.1 | v.1 | Jan-Jun 2012) - THE CRISIS TRANSFORMS THE INTERNATIONAL SYSTEM: EMERGING SOUTHERN CONNECTIONS - Austral, Revista (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
Access to the Complete Edition (n.1 | v.1 | Jan-Jun 2012) THE CRISIS TRANSFORMS THE INTERNATIONAL SYSTEM: EMERGING SOUTHERN CONNECTIONS